The impact of digitalization and economic openness on economic growth in ASEAN countries - Nurdiana, Erwin Dwi; Hariyani, Happy Febrina; Boedirochminarni, Arfida (Universitas Muhammadiyah Yogyakarta, 2023)
Digitalization with the Sustainable Development Goals (SDGs) Program is an essential means of encouraging the government to operate more openly and effectively, which can increase global economic growth. This research aims to assess how education, digitalization, and trade openness affect the economic development of ASEAN. This study uses independent variables in the form of government spending on education, individual internet users, foreign direct investment and consumer price inflation. The dependent variable is economic growth. This study uses the panel data regression method, from 2001 to 2020, with a cross-section of 7 ASEAN countries (Indonesia, Malaysia, Thailand, Laos, Singapore, the Philippines and Cambodia). According to the study, the economic growth in seven ASEAN countries is significantly influenced by government expenditure on education, individual internet users, and foreign direct investment. Empirical evidence confirms that digitalization positively impacts both the economy and society, as reflected in lower unemployment rates, improved quality of life, and increased access to public services and information. Furthermore, digitalization simplifies learning about various aspects and activities related to conducting trade, thereby contributing to economic growth. The limitation of the study is that there is no categorizing between developed and developing countries with different income groups that lead to different digital technology developments.